Recent Advances in 2D Lateral Heterostructures - Wang, Jianwei; Li, Zhiqiang; Chen, Haiyuan; Deng, Guangwei; Niu, Xiaobin (Nano-Micro Letters, 2019)
Recent developments in synthesis and nanofabrication technologies offer the tantalizing prospect of realizing various applications from two-dimensional (2D) materials. A revolutionary development is to flexibly construct many different kinds of heterostructures with a diversity of 2D materials. These 2D heterostructures play an important role in semiconductor and condensed matter physics studies and are promising candidates for new device designs in the fields of integrated circuits and quantum sciences. Theoretical and experimental studies have focused on both vertical and lateral 2D heterostructures; the lateral heterostructures are considered to be easier for planner integration and exhibit unique electronic and photoelectronic properties. In this review, we give a summary of the properties of lateral heterostructures with homogeneous junction and heterogeneous junction, where the homogeneous junctions have the same host materials and the heterogeneous junctions are combined with different materials. Afterward, we discuss the applications and experimental synthesis of lateral 2D heterostructures. Moreover, a perspective on lateral 2D heterostructures is given at the end. Highlights: 1 The tunable mechanisms of lateral heterostructures on both homogeneous junctions and heterogeneous junctions are summarized. 2 Electronic and photoelectronic devices with lateral heterostructures have been discussed. 3 Different types of contacts of 2D lateral heterostructures are classified. 4 Recent developments in synthesis and nanofabrication technologies of 2D lateral heterostructures are reviewed.